1993
DOI: 10.1111/j.1365-2621.1993.tb06141.x
|View full text |Cite
|
Sign up to set email alerts
|

Usable Energy Value of Selected Bulking Agents

Abstract: Four bulking agents-white wheat fiber, polydextrose, isomalt and oligofructose-were evaluated for usable energy values using young rats as the test model. The net increase observed in their carcass energy due to bulking agents fed over a 3-wk period was evaluated. Wheat fiber contained 0.9, polydextrose 0.8, isomalt 1.6, and oligofructose 1.5 calories/g. As a partial substitute for sugar, fat and/or flour, these bulking agents could effectively reduce the energy content of foods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
0
7
1
1
Order By: Relevance
“…Because of the lack of increase in carcass energy due to RS, we were unable, unlike in previous studies (Ranhotra et al, 1993;Ranhotra et al, 1994;Ranhotra et al, 1995), to calculate the energy value for RS, which appeared to be zero, as with silica. Virtually no differences were observed, for the various parameters measured, between the two sources of RS.…”
Section: Energy Value Of Resistant Starchcontrasting
confidence: 65%
See 1 more Smart Citation
“…Because of the lack of increase in carcass energy due to RS, we were unable, unlike in previous studies (Ranhotra et al, 1993;Ranhotra et al, 1994;Ranhotra et al, 1995), to calculate the energy value for RS, which appeared to be zero, as with silica. Virtually no differences were observed, for the various parameters measured, between the two sources of RS.…”
Section: Energy Value Of Resistant Starchcontrasting
confidence: 65%
“…This has been shown in many studies (McNeil, 1984;Cooley and Livesey, 1987;Miles et al, 1988). We also recently showed that was the case for wheat fiber, polydextrose and other bulking agents (Ranhotra et al, 1993). In that and related studies (Ranhotra et al, 1994;Ranhotra et al, 1995), we used a specific approach to assess energy value of food components.…”
Section: Introductionmentioning
confidence: 87%
“…The calorific value of the control drink was high being 70.2 kcal/100 ml. The significant reduction in calorific value of the formulation as compared to control was achieved by replacing fat and/or sucrose with inulin having calorific value of 1.5 kcal/g (Ranhotra et al 1993;Roberfroid et al 1993) and sucralose (high potency low calorie sweetener), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Nondigestible carbohydrates like inulin that pass through the digestive tract without being fermented or broken down reach the colon intact, where fermentation by bacteria takes place. Inulin has a low glycemic impact of 46 and a caloric value of 1.5 kcal/g (Ranhotra and others 1993; Mcdevitt‐Pugh and Meyer 2005). Because of the properties like low glycemic response and management of weight and others, inulin also acts as a texturizer, thereby enhancing sensory properties, and is useful in low glycemic index recipes.…”
Section: Inulin and Oligofructose: Structure And Importancementioning
confidence: 99%